THE STUDENTSâ ACHIEVEMENT IN UNDERSTANDING PRAGMATICS MEANING OF WRITTEN UTTERANCES - Syam, Nunung Anugerawati (Lembaga Perpustakaan Unismuh Makassar, 2012)
This research was attempted to find out the achievement of the sixth semester students of English Department of Muhammadiyah University of Makassar especially Academic Year 2008 in understanding pragmatics meaning of the written utterances.Â This study employed a Descriptive research method. The sample of this study consisted of 40 students of the Sixth Semester Students of English Department Muhammadiyah University of Makassar which was selected by using simple random sampling. The instrument of the study was an objective test in the form of checklist and identifying the locutionary, illocutionary, and perlocutionary acts of written utterances which consisted of 35 items. The test was administered to know the studentsâ achievement in understanding the pragmatic meaning of written utterances. The data obtained from the test was analyzed quantitatively.Â The mean score obtained from the test was 5, 87 for locutionary act, 6, 12 for illocutionary act, and 6, 09 for perlocutionary act. The data showed that the studentsâ achievement in understanding the pragmatics meaning of written utterances especially the three layers of speech acts was fair. Key Words: Pragmatics, locutionary act, illocutionary act, perlocutaionary act.Penelitian ini berusaha untuk mengetahui pencapaian mahasiswa semester enam Jurusan Bahasa Inggris Universitas Muhammadiyah Makassar terutama Tahun Akademik 2008 dalam memahami pragmatik arti dari ucapan-ucapan tertulis. Penelitian ini menggunakan metode Penelitian deskriptif. Sampel penelitian ini terdiri dari 40 siswa dari Semester Keenam Mahasiswa Jurusan Bahasa Inggris Universitas Muhammadiyah Makassar yang dipilih dengan menggunakan simple random sampling. Instrumen penelitian ini adalah tes objektif dalam bentuk checklist dan mengidentifikasi tindakan locutionary, ilokusi, dan perlocutionary dari ucapan-ucapan tertulis yang terdiri dari 35 item. Tes diberikan untuk mengetahui prestasi siswa dalam memahami makna pragmatis ucapan tertulis. Data yang diperoleh dari tes dianalisis secara kuantitatif. Rata-rata yang diperoleh dari tes itu 5,87 untuk tindakan locutionary, 6,12 untuk tindakan ilokusi, dan 6,09 untuk tindakan perlocutionary. Data menunjukkan bahwa prestasi siswa dalam memahami pragmatik yang arti dari ucapan-ucapan tertulis terutama tiga lapisan tindak tutur adalah seimbang.Kata Kunci: Pragmatik, tindakan locutionary, tindak ilokusi, tindakan perlocutaionary.